Modification of AlSi7Mg0.3 alloy by strontium - Náprstková, Nataša; Kuśmierczak, Sylvia; Cais, Jaromír (Manufacturing Technology Journal, 2013)
Alloy modifying is common practice for improving the structure of the material. One of often used material, where the modification is used is AlSi7Mg0.3 alloy. And modification of AlSi7Mg0.3 is often realized by strontium. The paper deals with an experiment that was realized at the Faculty of Production Technology and Management of Jan Evangelista Purkyně University in Ústí nad Labem, which dealt with the effect of modifications by strontium on the structure of AlSi7Mg0.3. In frame of its experiment were analyzed metallographic samples and were observed structures of unmodified and modified material on the microscope. Was evaluated result of modification on the structure.
Keywords: alloy; modification; silumin; Sr